2021
DOI: 10.7150/ijms.57821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MT2A on apoptosis and proliferation in HL60 cells

Abstract: Although accumulating evidence has revealed that metallothioneins (MTs) and its family member MT2A are strongly linked to the risk of various solid tumors, researches on the occurrence and development of acute myeloid leukemia (AML) have rarely been investigated. Here, we constructed a lentiviral vector with MT2A over-expression and the interfering plasmids with MT2A expression inhibition to study the influence of MT2A on the bioactivities of HL60 cells. After cells were infected with a lentiviral vector conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…MTs have been found to be associated with human cancers [ 40 , 41 ]. Reports have illustrated that MT2A is the modulator of cell proliferation and apoptosis in vitro and in vivo [ 42 , 43 ]. Results from in situ, in vitro, and in vivo studies have suggested that MT2A is an antitumor gene in gastric and colorectal cancers [ 11 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…MTs have been found to be associated with human cancers [ 40 , 41 ]. Reports have illustrated that MT2A is the modulator of cell proliferation and apoptosis in vitro and in vivo [ 42 , 43 ]. Results from in situ, in vitro, and in vivo studies have suggested that MT2A is an antitumor gene in gastric and colorectal cancers [ 11 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using transcriptomic sequencing, we screened metallothionein 2A (MT2A), a potential target gene of IPFSC-EVs, for its ability to inhibit knee arthrofibrosis. Studies have shown that MT2A plays an important role in regulating cell proliferation and inflammatory responses [24][25][26][27]. Therefore, exploring the effects of IPFSC-EVs on fibroblast proliferation in the inflammatory environment and the role of MT2A in this process is expected to provide new intervention targets for treating fibrotic diseases in clinical practice.…”
Section: Introductionmentioning
confidence: 99%